Synthesis and Biological Evaluation of Disubstituted Pyrimidines as Selective 5-HT2C Agonists - Juhyeon Kim; Yoon Jung Kim; Ashwini M. Londhe; Ae Nim Pae; Hyunah Choo; Hak Joong Kim; Sun-Joon Min (Molecules, 2019)
Here, we describe the synthesis of disubstituted pyrimidine derivatives and their biological evaluation as selective 5-HT2C agonists. To improve selectivity for 5-HT2C over other subtypes, we synthesized two series of disubstituted pyrimidines with fluorophenylalkoxy groups at either the 5-position or 4-position and varying cyclic amines at the 2-position. The in vitro cell-based assay and binding assay identified compounds 10a and 10f as potent 5-HT2C agonists. Further studies on selectivity to 5-HT subtypes and drug-like properties indicated that 2,4-disubstituted pyrimidine 10a showed a highly agonistic effect on the 5-HT2C receptor, with excellent selectivity, as well as exceptional drug-like properties, including high plasma and microsomal stability, along with low CYP inhibition. Thus, pyrimidine 10a could be considered a viable lead compound as a 5-HT2C selective agonist.